2014
DOI: 10.1002/cncr.28740
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐oncologist alliance as protection against suicidal ideation in young adults with advanced cancer

Abstract: Background Young adults with cancer are at increased risk for suicidal ideation. The impact of the patient-oncologist alliance on suicidal ideation has not been examined. This study examined the relationship between the patient-oncologist therapeutic alliance and suicidal ideation in young adults with advanced cancer. Methods Young adult patients (age 20-40 years; n=93) with incurable, recurrent, or metastatic cancer were evaluated by trained interviewers. Suicidal ideation was assessed with the Yale Evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 27 publications
4
93
0
2
Order By: Relevance
“…In addition, stress may impair the immunological mechanisms, and this can result in a poor response to treatment Cancer March 15, 2019 and added psychological stress, which can culminate in a suicide attempt. 21,27,31 Another factor that may explain why the risk of suicide varies significantly from one cancer to another is how patients cope with the diagnosis. Although recent studies have concluded that depression treatment in patients with cancer improves their quality of life, this has not been shown to increase survival or decrease the risk of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stress may impair the immunological mechanisms, and this can result in a poor response to treatment Cancer March 15, 2019 and added psychological stress, which can culminate in a suicide attempt. 21,27,31 Another factor that may explain why the risk of suicide varies significantly from one cancer to another is how patients cope with the diagnosis. Although recent studies have concluded that depression treatment in patients with cancer improves their quality of life, this has not been shown to increase survival or decrease the risk of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…As the oncologist often assumes the role of the PCP during treatment, this responsibility does fall to the oncology clinician. This kind of visit structure not only provides privacy to discuss sensitive subjects but also creates a safe space to enhance therapeutic alliance and to help the AYA patient take ownership of his or her medical care …”
Section: Discussionmentioning
confidence: 99%
“…[14] Yet we know very little about the end-of-life care that these young patients receive. Existing work has focused on the development of tools for end-of-life care planning,[5, 6] on psychological distress,[79] and on understanding adolescent patients’ wishes as they make cancer treatment decisions. [10] In addition, a single-center study in France evaluated care among 45 AYA cancer decedents and found high rates of symptoms and aggressive measures.…”
Section: Introductionmentioning
confidence: 99%